Effectiveness of acromioclavicular joint mobilization and physical therapy vs physical therapy alone in patients with frozen shoulder: A randomized clinical trial. (May 2022) - Rahbar, Mohammad; Ranjbar Kiyakalayeh, Sepideh; Mirzajani, Reza; Eftekharsadat, Bina; Dolatkhah, Neda
Objectives: The objective of this trial was to compare the efficacy of acromioclavicular joint mobilization and standard physical-therapy versus physical-therapy alone in the treatment of the frozen shoulder. Design: Single-blind randomized clinical trial. Setting: Outpatient setting. Subjects: Patients with frozen shoulder. Intervention: Participants were randomly allocated into mobilization + physical-therapy (n = 28), and physical-therapy alone (n = 28) groups for one month. Main Measures: The primary outcomes were the shoulder pain and disability index and the shoulder range of motion. The secondary outcome was the visual analogue scale. Measures were performed at the baseline, immediately and one month after the beginning of the treatment. Results: Visual analogue scale and the shoulder pain and disability index improved more significantly in the mobilization group compared to the physical-therapy group immediately [−4.63 (−5.58–−3.67) vs. −2.22 (−2.96–−1.47), P < 0.001 and −23.08 (−28.63–−17.53) vs. −13.04 (−17.93–−8.16), P = 0.008, respectively] and one month after the beginning of the treatment [−5.58 (−6.45–−4.72) vs. −3.61 (−4.60–−2.62), P < 0.001 and −33.43 (−40.85–−26.01) vs. −20.03 (−26.00–−14.07), P = 0.001, respectively]. Active abduction range of motion was also improved more significantly immediately after the treatment in the mobilization group compared to the physical-therapy group [25.83 (11.45–40.13) vs. 10.17 (1.02–19.15), P = 0.025], however there were no significant differences between two groups concerning other measured range of motions. Conclusions: Adding acromioclavicular mobilization to standard physical-therapy was more efficient in decreasing pain and disability and improving active abduction range of motion compared to standard physical-therapy in frozen shoulder patients.